Development of Augmented Reality Based Interactive E-LKPD to Improve Students’ Physics Concept Understanding on Alternative Energy - Helen Ulbrid; Desy Hanisa Putri; Netriani Veminsyah Ahda (Kasuari: Physics Education Journal (KPEJ), 2026)
This study aims to develop an interactive e-LKPD based on Augmented Reality (AR) on alternative energy materials at the high school level and describe the feasibility, effectiveness of improving students' understanding of concepts, and students' responses to the use of interactive e-LKPD utilizing Augmented Reality (AR). The research method applied is Research and Development with the ADDIE  model which includes analyze, design, development, implementation, and evaluation. The subjects of this study are 36 students in class X at one of the high schools in Bengkulu City. The product feasibility test was carried out by three validators consisting of two physics lecturers and one high school physics teacher. The data collection process is carried out through validation sheets, questionnaires given to students, and concept understanding tests through pretests and posttests. The findings of this study show that e-LKPD is very feasible with a percentage of 89.93% from three validators. The results of the students' responses were categorized as very good with a percentage of 90.34%. The results of  the pretest and posttest of the  AR-based interactive e-LKPD show the effectiveness of increasing the value of student concept understanding as shown by the N-Gain number  which is in the high category with a value of 0.80. Thus, Augmented Reality-based interactive e-LKPD has the potential to become a physics teaching material that supports improving students' understanding of concepts on alternative energy materials.